Adoption of Generative AI in Loyalty Programmes to Enhance Customer Engagement in South Africa - Digama, Ramaesela Hazel (University of the Witwatersrand, Johannesburg, 2025)
This research investigated the adoption of generative artificial intelligence (GenAI) in loyalty programmes and its potential to enhance customer engagement in South Africa. The study explores how businesses can leverage GenAI technologies to foster stronger relationships with their customers, increase participation in loyalty programmes, and drive growth and loyalty within the South African market. The research method involved conducting interviews with ten senior management professionals from both the business and technology sectors of an organisation planning to adopt GenAI in its loyalty programme. Using the Technology-Organisation-Environment (TOE) framework, the study assessed the factors influencing GenAI adoption. This approach provided a comprehensive evaluation of the technological, organisational, and environmental aspects impacting the successful implementation of AI-driven personalisation. Findings suggest that GenAI can drive hyper-personalisation, improving customer loyalty and engagement through tailored rewards and real-time experiences. However, challenges like departmental misalignment, knowledge gaps, and change management need to be addressed for successful adoption. Ethical concerns regarding privacy, algorithmic bias, and inclusivity also need to be considered. Recommendations include improving data quality, aligning strategies, addressing change management, and ensuring ethical AI practices to unlock GenAI's full potential. The contribution of this research will benefit key stakeholders, including organisations looking to enhance customer engagement with GenAI, policy bodies creating frameworks to support innovation and ethical practices, tech developers tailoring solutions for successful implementation, and the academic community advancing discussions on GenAI’s impact on consumer-focused innovation.
A research report submitted in fulfillment of the requirements for the Master of Management in the field of Digital Business, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Loyalty Programmes; Artificial Intelligenc; Generative AI; Technology-Organisation-Environment Framework; SDG-9: Industry, innovation and infrastructure; SDG-8: Decent work and economic growth